Kajian Penambahan RejIRE pada Aspal Modifikasi Crumb Rubber serta Kinerjanya pada Campuran Beraspal Panas - Mulyani, Sri; Nono, Nono; Suaryana, Nyoman (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Asphalt polymer has superior characteristics than conventional asphalt. Styrene Butadiene Styrene (SBS) is a polymer that has proven its performance in heavy traffic, but it must be imported and expensive. Crumb rubber have high potential to be used as an asphalt modifier. Asphalt modified crumb rubber has high viscosity and is not homogeneous, so that the utilization cannot be delayed. This reduces workability in the field. This study aims to obtain asphalt modified crumb rubber which is easier to use by adding materials that do not affect its performance. RejIRE is a low viscosity additive to restore the properties of bitumen on crumb rubber modified. Experiments were carried out by adding variations in RejIRE levels to crumb rubber modified asphalt to determine its characteristics. Continued investigation of the performance of hot paved mixtures for wearing courses compared to asphalt mixtures with Pen 60/70 asphalt and SBS modified asphalt mixtures. The result is the addition of 0.75% RejIRE on asphalt crumb rubber modification have high workability. Overall the performance of the mix with SBS modified asphalt is better, but the mixture of hot paved with modified asphalt crumb rubber has a resistance to permanent deformation superior to the other paved mixtures.